2020
DOI: 10.15190/d.2020.17
|View full text |Cite
|
Sign up to set email alerts
|

Is COVID-19 Fatality Rate Associated with Malaria Endemicity?

Abstract: COVID-19 (coronavirus disease 2019) is a disease caused by the coronavirus SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2). COVID-19 has yielded many reported complications and unusual observations. In this article, we have reviewed one such observation: an association between malaria endemicity and reduced reported COVID-19 fatality. Malaria-endemic regions have a significantly lower reported COVID-19 fatality rate as compared to regions where malaria is non-endemic. Statistical analyses show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Of notable importance, it has been observed that there are significantly lower COVID-19 clinical cases and fatalities in malaria-endemic regions than in non-endemic areas ( 19 , 22 , 34 ). Several host factors, including sociodemographic conditions, genetic background, and immune status, could be influencing the COVID-19 clinical evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Of notable importance, it has been observed that there are significantly lower COVID-19 clinical cases and fatalities in malaria-endemic regions than in non-endemic areas ( 19 , 22 , 34 ). Several host factors, including sociodemographic conditions, genetic background, and immune status, could be influencing the COVID-19 clinical evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we should also discuss the effect of polymorphism in relationship with other important disease. For example, Arshad AR, et al 10 proposed the potential role of CD-147, and potential malariainduced immunity and polymorphisms in COVID-19 patients. When an antimalarial drug is used for prophylaxis of COVID-19, the change of malarial parasite polymorphism resistant to the drug occurs 11 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several other factors that may have contributed to this reduction, such as symptomatic individuals being hesitant to visit health facilities due to fear of catching COVID-19 or stigma associated with being diagnosed with COVID-19, which suggests that COVID-19 infected individuals may not be seeking medical assessment [ 125 , 127 ]. Various studies have also described that reported COVID-19 fatality rate is significantly lower in malaria endemic than non-malaria endemic regions which may be attributed to a number of factors including lower capacity for testing, a lower mean population age or possibly cross-immunity or shared immunodominant epitopes between P. falciparum and COVID-19 [ 128 , 129 ].…”
Section: Point Of Care Covid-19 Testing Could Benefit Both Covid-19 A...mentioning
confidence: 99%